Direct and Indirect Effects of Strength-Based Parenting on Depression in Chinese High School Students: Mediation by Cognitive Reappraisal and Expression Suppression - Tang H; Lyu J; Xu M (Psychology Research and Behavior Management, 2022)
Hui Tang,1 Junxue Lyu,1 Meiyan Xu2 1School of Education, Zhaoqing University, Zhaoqqing, People’s Republic of China; 2Division of Biology, Dawang High School, Zhaoqqing, People’s Republic of ChinaCorrespondence: Hui Tang, Zhaoqing University, Zhaoqing Ave, Duanzhou District, Zhaoqing, Guangdong, 526061, People’s Republic of China, Email tanghui@zqu.edu.cnPurpose: A growing amount of research has been dedicated to the protective role of strength-based parenting in psychological distress. Strength-based parenting is a style of parenting in which parents are conscious of their children’s strengths, and encourage them to develop and make use of those strengths. However, the mechanisms linking strength-based parenting to depression are not well known. Drawing on the social–emotional learning model, this study examined the association between strength-based parenting and depression and the indirect role of emotion regulation (ie, cognitive reappraisal and expression suppression).Materials and Methods: A total of 750 Chinese middle school students from two middle schools completed questionnaires comprising the Strength-based Parenting Scale, the Emotion Regulation Scale, the Center for Epidemiologic Studies Depressive Scale, and sociodemographic characteristics. A total of 695 students provided accurate responses to the two validity check questions, and were thus retained in the final study sample. Of the final sample, 348 (50.1%) were girls, and the respondents overall had an average age of 16.22 years. The direct and indirect paths from strength-based parenting to depression were analyzed using structural equation modeling.Results: The results showed that strength-based parenting negatively predicted depression and cognitive reappraisal, while strength-based parenting positively predicted depression. Strength-based parenting indirectly predicted depression through cognitive reappraisal and expression suppression.Conclusion: These findings suggest an underlying process by which high strength-based parenting resists depression by increasing cognitive reappraisal and decreasing expression suppression. It is necessary to implement a comprehensive intervention strategy that focuses on strength-based parenting and emotion regulation (eg, cognitive reappraisal).Keywords: strength-based parenting, depressive, cognitive reappraisal, expression suppression, Chinese